2022
DOI: 10.17233/sosyoekonomi.2022.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Birleşme ve Satın Alma Gerçekleştiren Firma Yöneticilerinin Aşırı Güven Davranışlarının Firma Değeri Üzerine Etkisi

Abstract: This study aims to examine the effect of overconfidence behaviours of the managers of the companies whose stocks are traded in Borsa Istanbul on the firm value. In the study, a model was created for Tobin q (Model 1), stock market value (Model 2) and enterprise value (Model 3). As a result of the study, a negative relationship was determined between the change in firm value and the overconfidence variable. According to this result, if the managers performing mergers and acquisitions are overconfident, the inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These factors contribute to the final M&A transaction price being determined at a higher price than the preacquisition market value of the target firm, and the difference between this price and the fair value can be interpreted as a premium at the time of the M&A transaction (Bebenroth & Ahmed, 2023). Unfortunately, this premium ultimately negatively affects the interests of acquiring company shareholders (Can & Dizdarlar, 2022).…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors contribute to the final M&A transaction price being determined at a higher price than the preacquisition market value of the target firm, and the difference between this price and the fair value can be interpreted as a premium at the time of the M&A transaction (Bebenroth & Ahmed, 2023). Unfortunately, this premium ultimately negatively affects the interests of acquiring company shareholders (Can & Dizdarlar, 2022).…”
Section: Results Discussionmentioning
confidence: 99%
“…Specifically, they revealed that CEO hubris, or excessive self-confidence, quantitatively explains a significant portion of merger and acquisition premiums. Recent corporate performance and favorable media coverage significantly influence CEO hubris and self-confidence, which has a negative impact on the interests of acquiring company shareholders in mergers and acquisitions (Can & Dizdarlar, 2022). As a result, CEO's personal judgements may influence corporate mergers and acquisitions rather than careful methodical decision-making processes, and if the market (shareholders) is concerned about this trend, it may respond negatively to high transaction price.…”
Section: Mergers and Acquisitions Transaction Pricementioning
confidence: 99%
“…Transitioning to the concept of firm value (FV) focuses on a firm's worth or market capitalization. It represents all assets, including tangible and intangible assets, and the value of any outstanding debt (Au et al, 2021;Can & Dizdarlarjk, 2022;Kang & Park, 2021). The worth of a company is essential to investors, shareholders, and potential acquirers, as it indicates the firm's economic status and prospects.…”
Section: Introductionmentioning
confidence: 99%